The Effects of Gardeniae Fructus Aqua-Acupuncture on Liver Injury of Rats Induced by CCI4 ( - Park, Hee-Soo; Park, Joung-Hyun (Korean Pharmacopuncture Institute, 2000)
This is the study of the effects of Aqua-acupuncture with Gardeniae Fructus on thc recovery of rat's liver which was damaged by 0.3ml/ea of CCI4. Rats were divided into 4 groups; Normal-group(None treated group), Control-group(Not treated after CCI4-intoxicated), Exp. I(Treated with Saline Aqua-acupuncture after CCI4-intoxicated) and Exp. ll(Treated with Gardeniae Fructus Aqua-acupuncture after CCI4-intoxicated). Biochemical assays for each serum enzyme activities of AST, ALT, Albumin, LDH, γ-GT, TG and Total cholesterol were performed. The results were summarized as follows: 1. AST activities in serum significantly decreased in the Gardeniae Fructus Aqua-acupuncture treated group after CCI4-intoxicated. In companson with Saline-treated group after CCI4-intoxicated, the Gardeniae Fructus Aqua-acupuncture treated group *The professor of Dept. of Acupuncture & Moxibustion, 2. At T activities in serum significantly decreased in the Gardeniae Fructus Aqua-acupuncture treated group after CCI4-intoxicated. In com pan son with Saline-treated group after CCI4-intoxicated, the Gardeniae Fructus Aqua-acupuncture treated group after CCI4-intoxicated worked effectively to rat's damaged liver. 3. Albumin in serum increased in the Gardeniae Fructus Aqua-acupurkture treated group after CCI4-intoxicated. 4. LDH in serum significantly decreased in the Gardeniae Fructus Aqua-acupuncture treated group after CCI4-intoxicated. In comparison with Saline-treated group after CClcintox icated, the Gardeniae Fructus Aqua acupuncture treated group after CCI4-intoxicated worked highly effectively to rat's damaged liver. 5. γ-GT In serum significantly decreased In the Gardeniae Fructus Aqua-acupuncture trea ted group after CCI4-intoxicated. In compan son with Saline-treated group after CCI4-intoxicated, the Crardeniae Fructus Aqua-acupuncture treated group after CCI4-intoxicated was not recognized significantly. 6. TG in serum significantly decreased in the Gardeniae Fructus Aqua-acupuncture treated group after CCI4-intoxicated. In comparison with Saline-treated group after CCI4-intoxicated, the Gardeniae Fructus Aqua-acupuncture treated group after CCI4-intoxicated worked highly effectively to rat's damaged liver. 7. Total cholesterol in serum decreased in the Gardenias Fructus Aqua-acupuncture treated group after CCI4-intoxicated. In comparison with Saline-treated group after CCI4-intoxicated, the Gardeniae Fructus Aqua-acupuncture treated group after CCI4-intoxicated worked highly effectively to rat's damaged liver. The results from ahove show that the Gardeniae Fructus Aqua- acupuncture has highly effects on the damaged liver caused by . Therefore it is expected that the Gardeniae Fructus Aqua- acupuncture could be used to cure the damaged liver.